(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
An original, multicomponent technology is proposed for extracting precious, base, and rare-earth elements from Kyrgyzstan’s technogenic wastes. The core of the process is electro-physical ionisation (EPI) enhanced by cavitation-assisted ultrasound and implemented in a spatially distributed multi-electrode configuration. The study pursued a dual objective: (i) to formulate the physico-chemical rationale that ensures maximal selectivity and high energy efficiency, and (ii) to model operating regimes that minimise the generation of secondary pollutants. Feedstocks included concentrator tailings, metallurgical slags, and sludges accumulated in the country’s key mining provinces. A response-surface experimental design enabled fine-tuning of the critical parameters: potential 6–12 V, inter-electrode gap 1.0–1.5 cm, electrolyte molarity 0.5–1 M, acoustic power < 300 W, and treatment duration 30–65 min. The result was record extraction efficiencies: Cu — 96.8 %, Zn — 93.5 %, Ag — 92.1 %, Au — 88.5 %. For the rare-earth representatives, La and Nd, the respective values reached 79.7 % and 81.1 %. The purity of the recovered precipitates, verified by combined ICP-OES / SEM-EDX analysis, exceeded 99.8 ‰ (Cu) and 99.5 ‰ (Au, Ag). The synergy of ultrasonic cavitation and the multi-electrode field lowers the energetic barrier of electrochemical reactions, disaggregates the solid phase, accelerates mass transfer, and ensures uniform current distribution, thus preventing anode passivation. Comparison with conventional hydro- and pyrometallurgical routes revealed an order-of-magnitude reduction in energy consumption and complete elimination of hazardous reagents. The developed approach not only paves the way for comprehensive recycling of accumulated wastes—mitigating environmental risks—but also establishes an alternative mineral resource base for critical metals, capable of providing an additional impetus to the economy of the Kyrgyz Republic